Randomized clinical trial of transcutaneous electrical posterior tibial nerve stimulation versus lateral internal sphincterotomy for treatment of chronic anal fissure. (October 2015) - Youssef, Tamer; Youssef, Mohamed; Thabet, Waleed; Lotfy, Ahmed; Shaat, Reham; Abd-Elrazek, Eman; Farid, Mohamed
Abstract: Objectives: The objective of this study was to evaluate the efficacy of transcutaneous electrical posterior tibial nerve stimulation in treatment of patients with chronic anal fissure and to compare it with the conventional lateral internal sphincterotomy. Patients and methods: Consecutive patients with chronic anal fissure were randomly allocated into two treatment groups: transcutaneous electrical posterior tibial nerve stimulation group and lateral internal sphincterotomy group. The primary outcome measures were number of patients with clinical improvement and healed fissure. Secondary outcome measures were complications, VAS pain scores, Wexner's constipation and Peascatori anal incontinence scores, anorectal manometry, and quality of life index. Results: Seventy-three patients were randomized into two groups of 36 patients who were subjected to transcutaneous electrical nerve stimulation and 37 patients who underwent lateral internal sphincterotomy. All (100%) patients in lateral internal sphincterotomy group had clinical improvement at one month following the procedure in contrast to 27 (75%) patients in transcutaneous electrical nerve stimulation group. Recurrence of anal fissure after one year was reported in one (2.7%) and 11 (40.7%) patients in lateral internal sphincterotomy and transcutaneous electrical nerve stimulation groups respectively. Resting anal pressure and functional anal canal length were significantly reduced after lateral internal sphincterotomy. Conclusion: Transcutaneous electrical posterior tibial nerve stimulation for treatment of chronic anal fissure is a novel, non-invasive procedure and has no complications. However, given the higher rate of clinical improvement and fissure healing and the lower rate of fissure recurrence, lateral internal sphincterotomy remains the gold standard for treating chronic anal fissure. Highlights: The objective was to evaluate the efficacy of TENS in treatment of chronic anal fissure in comparison with LIS. 75% of patients in TENS group had clinical improvement one month following the procedure. All patients in LIS group had clinical improvement one month following the procedure. Recurrence of anal fissure after one year was reported in 2.7% and 40.7% of patients in LIS and TENS groups respectively. LIS remains the gold standard for treating chronic anal fissure.